Measuring Irrationality in Financial Markets - Schädler, Tobias (Archives of Business Research, 2019)
This paper presents the measurement of irrationality contained in the continuous pricing of individual stocks. Irrationality is used to extend the concept of historical volatility by decomposing historical stock quotes into frequencies via Fourier transformation. The analysis in the frequency domain enables clustering of the contributions of short and long-term fluctuations to the overall price changes. With the resulting ratio it is possible to rank stocks within an index according to their specific fluctuation profile. The analysis is performed on daily stock quotes over a period of 20 years (1997-01-02 until 2016-12-30). Although the analysis presented here focuses on the stock market, the concept of irrationality is transferable to other financial markets as for bonds, housing prices or derivatives as well as to different time periods.